2014
DOI: 10.1371/journal.pone.0105147
|View full text |Cite
|
Sign up to set email alerts
|

Phs1 and the Synthesis of Very Long Chain Fatty Acids Are Required for Ballistospore Formation

Abstract: The production and dissemination of spores by members of the fungal kingdom is a major reason for the success of this eukaryotic lineage in colonizing most terrestrial ecosystems. Ballistospores are a type of spore produced by basidiomycete fungi, such as the mushrooms and plant pathogenic rusts. These spores are forcefully discharged through a unique liquid-drop fusion mechanism, enabling the aerosolization of these particles that can contribute to plant disease and human allergies. The genes responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Recently, Ianiri et al reported that 3-hydroxyacyl-CoA dehydratase gene Phs1 is not only responsible for the very long chain fatty acid biosynthesis, but also for the ballistospores-shooting in Sporobolomyces sp. IAM 13481 [31]. However, we found this Phs1 gene in the both S. pararoseus NGR and R. toruloides genomes.…”
Section: Comparative Analysis Of Protein Families and Genesmentioning
confidence: 63%
“…Recently, Ianiri et al reported that 3-hydroxyacyl-CoA dehydratase gene Phs1 is not only responsible for the very long chain fatty acid biosynthesis, but also for the ballistospores-shooting in Sporobolomyces sp. IAM 13481 [31]. However, we found this Phs1 gene in the both S. pararoseus NGR and R. toruloides genomes.…”
Section: Comparative Analysis Of Protein Families and Genesmentioning
confidence: 63%
“…Strand-specific libraries were prepared from RNA isolated from Sporobolomyces sp. 1) yeast cells grown in the presence and in the absence of 5 μg/ml of PAT (two biological replicates for each of two samples), 2) yeast cells collected from YPD agar medium after 2 days of incubation, 3) ballistospore cells fired on a YPD agar mirror plate, a spore dispersal system that we previously described [ 37 ]. The table in Additional file 1 summarizes the samples used for RNA extraction, the type of libraries generated and their use for downstream analysis (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the incubation in the presence of PAT, Sporobolomyces sp. RNA was extracted also from cells collected on YPD agar after two days of growth, and from fired ballistospores collected from a mirror YPD plate [ 37 ]; in the present study these data were only used for the generation of the Sporobolomyces sp. reference transcriptome (Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…IAM 13481 were used to investigate the molecular basis of the intriguing mechanism of ballistospore formation and dispersal that is unique to basidiomycete fungi. This property can be evaluated in the laboratory by the production of a mirror image of a culture from one Petri dish onto an uninoculated second dish [ 193 ]. The screen of more than 5000 transformants led to identification of 18 mirror mutants unable to shoot spores to produce the mirror image.…”
Section: Fungal Species and Biological Questions In Which Amentioning
confidence: 99%
“…Strikingly, PHS1 is an essential gene in other fungi, and its identification in a Sporobolomyces sp. mutant was fortuitous as the T-DNA inserted within the last intron of the gene and past the essential amino acid residues required for function, which resulted in the production of an altered transcript yet still viable phenotype [ 193 ].…”
Section: Fungal Species and Biological Questions In Which Amentioning
confidence: 99%